Sonoporation, a Novel Frontier for Cancer Treatment: A Review of the Literature - Martina Ricci; Elisa Barbi; Mattia Dimitri; Claudia Duranti; Annarosa Arcangeli; Andrea Corvi (Applied Sciences, 2024)
Sonoporation has garnered significant attention for its potential to temporarily permeabilize cell membranes through the application of ultrasound waves, thus enabling an efficient cellular uptake of molecules. Despite its promising applications, the precise control of sonoporation remains a complex and evolving challenge in the field of cellular and molecular biology. This review aims to address two key aspects central to advancing our understanding of sonoporation. Firstly, it underscores the necessity for the establishment of a standardized methodology to validate and quantify the successful entry of molecules into target cells. This entails a critical examination of existing techniques and the identification of best practices to ensure accurate, reliable, and reproducible results. By establishing a common framework for assessing sonoporation outcomes, researchers can enhance the reliability and comparability of their experiments, paving the way for more robust findings. Secondly, the review places particular emphasis on the detailed analysis of various acoustic parameters as reported in the papers selected from the literature. Among these parameters, acoustic intensity (specifically, ISPTA) emerges as a pivotal factor in sonoporation studies. Furthermore, this review delves into the exploration of the elastic modulus and its significance in sonoporation mechanisms and associated challenges. This knowledge can inform the development of more effective strategies to optimize sonoporation protocols. In summary, this review not only highlights the pressing need for a standardized approach to verify molecule entry into cells but also delves into the search for an effective frequency and acoustic intensity for in vivo and in vitro applications.